2019
DOI: 10.1002/cam4.2110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological characteristics and survival analysis of 4594 Japanese patients with melanoma

Abstract: Background The incidence of melanoma among those of an Asian ethnicity is lower than in Caucasians; few large‐scale Asian studies that include follow‐up data have been reported. Objectives To investigate the clinical characteristics of Japanese patients with melanoma and to evaluate the prognostic factors. Methods Detailed patient information was collected from the database of Japanese Melanoma Study Group of the Japanese Skin Cancer Society.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 30 publications
2
101
1
3
Order By: Relevance
“…In this study, the incidence of cytoband gains was significantly higher in AMs than in NAMs. This result may partially explain the generally poorer prognosis for AM …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the incidence of cytoband gains was significantly higher in AMs than in NAMs. This result may partially explain the generally poorer prognosis for AM …”
Section: Discussionmentioning
confidence: 99%
“…This helps to explain why most patients with AMs would not benefit from BRAF inhibitors (Table S10). Besides, compared with NAMs, lower mutation burdens are found in AMs, which have previously demonstrated a lower response rate to checkpoint inhibitors . The co‐occurrence of several structural variants may change the cancer cell phenotype, making it more resistant to therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Four of the present five stage IV patients showing elevated sNSE but not sLDH had mucosal‐type melanomas. The mucosal type was reported in 10% of Japanese melanoma patients, 19 but clinical trials and real‐world data in Japan have shown that the mucosal type accounts for 25–40% of the melanoma patients who required systemic therapy in the advanced stage 20,21 . Because of the limited number of cases, it is necessary to examine greater numbers of melanoma patients to determine the precise usefulness of sNSE as a biomarker of mucosal melanoma and its potential superiority to sLDH.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR of nivolumab monotherapy in a Japanese population was again much lower than that in a Caucasian population according to post-marketing surveillance analysis in Japan (22.2%) [51]. Notably, the most common subtype of melanoma in Japan was acral lentiginous melanoma (ALM) (40.4%) [52], while the ratio of ALM in a non-Hispanic, white-skinned population in the United States was much lower (1%) [53]. A previous report also suggested that the ORR of anti-PD1 Abs for ALM and mucosal melanoma was lower in a Caucasian population [54].…”
Section: Efficacy Of Anti-pd1 Antibody Monotherapy Against Advanced Mmentioning
confidence: 95%